Reparations for slavery in international law: transatlantic enslavement, the maangamizi, and the making of international law - Schwarz, Katarina (Oxford University Press, 2022)
From the 'transatlantic slave trade' to the maangamizi -- The maangamizi and the making of international law -- Adjudicating the 'past' : the impact of time on reparability -- Towards a theory of reparatory justice -- Expanding understandings of reparatory justice through multiple modalities of redress --The causal chains connecting historical enslavement and contemporary redress -- Reparatory justice in transition.